EFEKTIVITAS PENERAPAN PERATURAN DAERAH NOMOR 2 TAHUN 2014 DALAM MEWUJUDKAN KOTA JAMBI YANG BEBAS PROSTITUSI - Senjaya, Burlian (JISIP UNJA (Jurnal Ilmu Sosial Ilmu Politik Universitas Jambi), 2018)
This article of the result of this study aims to describe the level of the effectiveness of the enforcement of local regulation Number 2nd Year 2014 about the eradication of prostitution and immoral actions in Jambi Municipality by using achievement indicator of goal, productivity, and efficiency. In this study the writer found that local regulation is effective when measured from short and medium term goal achievement indicator, but that regulation needs to be reinforced to reach long term goal in order to create Jambi Municipality which is free from prostitution and immoral actions. It is also effective when measured from productivity indicator; it is proved that the local regulation can be legal force which is possible to mobilize all components of society and resources owned by Jambi Municipality in doing eradication of prostitution so that the enforcement of the regulation has reached the maximal output. Besides that, the reinforcement of this regulation is also effective when measured from efficiency indicator in which local regulation Number 12 Year 2014 has had a significant impact on prostitution eradication in Jambi Municipality. It can be seen from the output obtained in reaching the goal of the enforcement of the local regulation.